(3fjd GdQGFO ef Gdfjd GdRGFOs - (3CMeO Hf eMeO Hf YeQ GdMLGRjs
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd ef GdSeGA eGA Hg GdCQV HYO ehJ CMjGgG hHYO abO SCdfi HYV GdCUObGA eG GTJed Ydjg HMQ Gdfjd ef GdRjGOI ai cd YGe s
(3BNQgG (B:s
(3BNQ eGajg eHdZ GdRjGOI SfI (B920 (3g` s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ ai MjGI GdeDda s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdLZQGajG h GdHdOGfs